Semantic Lexical Alignment For Domain-Specific Ontologies. - Abu-Shareha, Ahmad Adel; Mandava, Rajeswari; Ramachandram, Dhanesh (2009)
Domain-specific ontologies encode reusable domain vocabulary and represent established domain semantics.